Cardiometabolic Biomarkers and Prediction of Kidney Disease Progression: The eGFR Cohort Study - Elizabeth L. M. Barr; Federica Barzi; Phillip Mills (Kulkalgal); Maria Nickels; Sian Graham; Odette Pearson; Varuni Obeyesekere; Wendy E. Hoy; Graham R. D. Jones; Paul D. Lawton; Alex D. H. Brown; Mark Thomas; et al. (Canadian Journal of Kidney Health and Disease)
Background: Traditional markers modestly predict chronic kidney disease progression in Aboriginal and Torres Strait Islander people. Therefore, we assessed associations of cardiometabolic and inflammatory clinical biomarkers with kidney disease progression among Aboriginal and Torres Strait Islander people with and without diabetes. Objectives: To identify cardiometabolic and inflammatory clinical biomarkers that predict kidney disease progression in Aboriginal and Torres Strait Islander people. Design: Prospective observational cohort study Setting: Northern Territory, Australia Participants: Aboriginal and Torres Strait Islander participants of the estimated glomerular filtration rate (eGFR) study with (n = 218) and without diabetes (n = 278) Measurements: Baseline biomarkers (expressed as 1 standard deviation increase in logarithmic scale), plasma kidney injury molecule-1 (pKIM-1) (pg/ml), high-sensitivity troponin-T (hs-TnT) (ng/L), troponin-I (hs-TnI) (ng/L), and soluble tumor necrosis factor receptor-1 (sTNFR-1) (pg/ml) were assessed in 496 adults. Annual change in eGFR (ml/min/1.73 m 2 ) and a composite kidney outcome (first of ≥30% eGFR decline with follow-up eGFR <60 ml/min/1.73 m 2 , initiation of kidney replacement therapy or kidney disease-related death) over a median of 3 years. Methods: Linear regression estimated annual change in eGFR (ml/min/1.73 m 2 ). Cox proportional hazards regression estimated hazard ratio (HR) and 95% CI for developing a combined kidney health outcome. Results: In individuals with diabetes, but not those without diabetes, higher baseline hs-TnT (−2.1 [−4.1 to −0.2], P = .033) and sTNFR-1 (−1.8 [−3.5 to −0.1], P = .039) predicted mean (95% CI) eGFR change, after adjusting for age, gender, baseline eGFR, and urinary albumin-to-creatinine ratio. Baseline variables explained 11% of eGFR decline variance; increasing to 27% ( P < .001) with biomarkers. In diabetes, hs-TnT and hs-TnI were significantly associated with increased risk of kidney health outcomes. Limitations: Limitations included potential chronic kidney disease misclassification from single creatinine and albumin measurements, limited adjustment for covariates due to a small sample size, and short follow-up restricting long-term outcome assessment. Conclusions: Cardiovascular, kidney, and inflammatory biomarkers are likely associated with kidney function loss in diabetes, with particularly prominent associations for cardiac injury markers.